2014
DOI: 10.1103/physrevb.90.165301
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic polaron localization and spontaneous symmetry breaking: Comparison of cation-site acceptors in GaN and ZnO

Abstract: The behavior of cation substitutional hole-doping in GaN and ZnO is investigated using hybrid density functional calculations. Our results reveal that Mg substitution for Ga (MgGa) in GaN can assume three different configurations. Two of the configurations are characterized by the formation of defect-bound small polaron (i.e., a large structural distortion accompanied by hole localization on one of the neighboring N atoms). The third one has a relatively small but significant distortion that is characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…For the isolated Li Zn and Na Zn acceptors, we find that both exhibit a dual behavior, as first reported by Lany and Zunger [27,28] using a Koopmans corrected semilocal functional, and later by Sun et al [56] using the HSE(0.375, [28]. In the neutral charge state, two distinct acceptor states can occur [27,28]: (i) a metastable shallow state, where the hole is bound in an anisotropically delocalized hostlike state [56], and (ii) a deep ground state, which can be reached through a sizable symmetry-breaking lattice distortion. As shown in Fig.…”
Section: A Formation Energies Thermodynamic Charge-state Transitionsupporting
confidence: 86%
“…For the isolated Li Zn and Na Zn acceptors, we find that both exhibit a dual behavior, as first reported by Lany and Zunger [27,28] using a Koopmans corrected semilocal functional, and later by Sun et al [56] using the HSE(0.375, [28]. In the neutral charge state, two distinct acceptor states can occur [27,28]: (i) a metastable shallow state, where the hole is bound in an anisotropically delocalized hostlike state [56], and (ii) a deep ground state, which can be reached through a sizable symmetry-breaking lattice distortion. As shown in Fig.…”
Section: A Formation Energies Thermodynamic Charge-state Transitionsupporting
confidence: 86%
“…This is similar to other theoretical results obtained in Refs. [3][4][5]. Strongly localized nature of this small polaron leads to the predicted wide PL band, with the Franck-Condon shift of 0.43 eV, which is a signature of a deep defect state.…”
Section: B Why Localized Small Polaron States Of Mg Ga Are Not Obsermentioning
confidence: 88%
“…As mentioned above, three distinct defect states of neutral Mg Ga ,5 with different lattice configurations of similar energies are two localized small polarons and one anisotropically delocalized shallow state. The latter is delocalized in [ 1120 ] direction of wurtzite GaN and localized in all other directions.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…They also predicted that the Li Zn defect in ZnO may have a dual nature, where, in addition to the deep localized state, a shallow acceptor state may exist at about 0.21 eV above the valence band and be revealed in certain experimental conditions [18]. DFT calculations based on hybrid functional schemes predicted a binding energy of 0.75 eV [19,20] and 0.46 eV [21] for the Li Zn acceptor in ZnO. Carvalho et al [22] concluded that, by using different pseudopotentials and functionals, the calculated binding energy of the Li Zn acceptor varies between 0.6 and 1.1 eV.…”
Section: Introductionmentioning
confidence: 97%